New Interaction Paradigm of Ecological, Social and Economic Structures of Human Activity - Buletova, Natalya Yevgenyevna; Gorelova, Irina Valerievna; Golomanchuk, Ada Vladimirovna; Orlova, Yelena Roaldovna (Economy of Regions, 2015)
Realities of the XXI century demand searching and grounding measures on changing economic, political, and the main thing, ideological institutions that determine trends of evolution and managing vital human activity at national and over-national levels. Using synergetic approach, the authors made an attempt to synthesize conclusions and main theses of neo-institutionalism theory, onto-psychology, as well as results of biological evolution for determining the way to overcome global ecological crisis at nano-level and to form a model of the mankind's optimal evolution on the base of principle “priorities through parities”, using DNA-symbol as a code of survival, through co-evolution of economy and ecology. The main problem, existing even in economically developed countries, is the realization of the fact that the paradigm of the stationary economy is the only condition for the mankind's survival. To solve this problem serious transformation of ideological institutions is necessary, at the expense of comprehensive and based on onto-psychological methods program of ecological literacy, that should harmonically blend with the presented by the authors triads of state strategic management and achieving the goal of development. It is the transformation of the national matrix, content and direction of which are set in order to ensure a balance of interests of all participants in ecological and economic development, will lay the necessary rules, both formal and informal, in the style of human behavior, social groups, the national economy. Realization of the program ecological literacy within the national policy on ecological development of the regions is one of the most important conditions for a natural, not imposed from the outside, prepare to use the paradigm of a sustainable economy as the basis of economic, political and ideological institutions of modern society, which is primarily the formation of a new paradigm of human device - devices nano-level decision-making, consumer behavior.